The Effect Of Educational Videos About Anemia On The Knowledge Of Pregnant Women In The Working Area Of The Satellite Health Center Of Bandar Lampung - Dea Fitria Sela; Nopi Anggista Putri; Beniqna Maharani Besmaya; Yunita Anggriani; Dewi Fatmawati; Asri Meiwulantari; Ghina Hamidah Hanun; Agustini, Agustini (Sean Institute, 2024)
Anemia during pregnancy is a serious health problem and has a negative impact on maternal and fetal health. Data from the Bandar Lampung Health Office in 2022 shows anemia 10.08% of 19,592 pregnant women. One of the provisions of health education to increase pregnant women's knowledge about anemia is by providing education using video media to help pregnant women understand about anemia and obtain proper information. This study aims to determine the effect of educational videos about anemia on pregnant women's knowledge. The research method used Pre-Experimental with One Group Pre-Posttest Design approach. The population in this study were all Primigravida pregnant women at the Satelit Public Health Center Bandar Lampung, totaling 15 people, while the samples taken were 15 people using Total Sampling. This research was conducted in August 2024 in the Working Area of Satelit Public Health Center Bandar Lampung. Data analysis in this study used T-Test. The results of the study obtained questionnaire data before and after the intervention with average results before (70.33) and after (93.00). The analysis results showed a significant increase in pregnant women's knowledge about anemia. Statistical analysis showed a p-value of 0.000 (P<0.05), concluding that there is an effect of Educational Video About Anemia on Pregnant Women's Knowledge in the Working Area of Satelit Public Health Center Bandar Lampung. The results of this study show that visual media such as educational videos can be effective in increasing pregnant women's health knowledge. Therefore, it is expected that officers can apply more broadly in public health programs, one of which is conducting educational counseling using videos.